Content of fatty acids in meat of snails of different types - Данілова, І. С. (Scientific Progress & Innovations, 2018)
The data on fatty acid composition of snail meat of the following species: Helix pomatia, Helix aspersa maxima and Helix aspersa muller are presented. Unsaturated fatty acids are fatty acids that contain at least one double bond in the chain of fatty acids. Unsaturated fatty acids have a low melting point and are liquid in consistency, are easier assimilated by the human body than saturated fatty acids. Saturated fatty acids are fats of animal origin, entering the body from meat products, oils, eggs, sausages and dairy products. They differ from other fats in that they remain solid even at room temperature. Saturated fats are needed for energy, they are involved in the structure of cells. That is why their surplus leads to overweight accumulation, as well as to an increase in cholesterol in the body, heart disease and even some types of cancer. If a person does not consume saturated fatty acids, the body will be able to synthesize them from another food. However, for the body it is also superfluous, so in small quantities such fats are needed. The research was done in accordance with the procedures described in the relevant State Standards of Ukraine “Determination of fatty acid spectrum – SSU ISO 5508-2001. Fats and oils of animal and vegetable origin. Gas chromatography analysis of methyl esters of fatty acids. Sample preparation – SSU ISO 5509-2002. Fats of animal and vegetable origin and oils. Preparation of methyl esters of fatty acids”. Chromatographic analysis of fatty acids was performed on a Trace Ultra gas chromatograph with a flame-ionization detector, on a capillary column SP-2560 (Supelco). The limit of the method is 0.01%. We have formed three groups of different snail species that are used for food purposes: Helix pomatia collected in the wet weather and in the morning, Helix aspersa maxima and Helix aspersa muller got from the farm «SNAIL 2016» (Ukraine), for which we express our gratitude to the owner. Snails of each species were the same in size and weight. Since our data were first obtained not only in Ukraine but also globally, it was not possible to compare them with the data of other authors. The results were processed statistically. As a result of our studies on the content of fatty acids in the meat of snails it is found that the mass fraction of unsaturated fatty acids is most commonly found in Helix pomatia snail meat and amounts to 132.14 % up to the amount of fatty acids. It is this fact that indicates the nutritional value of these snails. Saturated fatty acids enrich the meat of Helix aspersa muller snails and reaches 33.96% to the sum of fatty acids, and also in these types of snails ω-3 fatty acids to ω-6 fatty acids is 1:4.3. Such a combination of ω-3 fatty acid to ω-6 fatty acid is best for a good assimilation and well-being of a person who will consume such meat. It should be noted that the total content of fatty acids in the meat of snails varies in the following ranges: Helix pomatia 158.29, Helix aspersa maxima 148.97, and Helix aspersa muller 139.78. Attention should be drawn to the ratio of unsaturated fatty acids, namely mono-, di- and polyunsaturated acids in meat of each type of snail. According to our data in the meat of snails: Helix pomatia reaches 15.68: 37.67: 78.79, Helix aspersa maxima – 21.23: 31.61: 66.22, Helix aspersa muller – 26.7: 24.45 : 54.67. However, if you compare the meat of snails with the meat of black African ostrich, the fatty acid content of these two animals is very different. Thus, snail meat contains up to 14.36% palmitic acid, 13.98% stearic acid, 26.54% oleic acid, 37.67% linoleic acid and, of course, ω-3 and ω-6 fatty acids 7.49% and 51.12% respectively, depending on the type of snail, while in ostrich meat these figures reach only a tenth or even hundredth share. Thus, it can be argued that Helix pomatia, Helix aspersa maxima and Helix aspersa muller can be used as a valuable source of saturated and unsaturated fatty acids. For the first time in Ukraine, we studied the fatty acid content of Helix pomatia, Helix aspersa maxima, Helix aspersa muller snails, which are edible species and are used as a delicacy. Snail meat is a valuable source of essential fatty acids. Of the 21 acids in each experimental species, the snail contains both saturated and unsaturated fatty acids. The saturated ones contain: kapron, palmitic, stearin, myristic, arachin, capryl, lauric, behenic, kaprinic, heptadecanic and unsaturated: oleinic, palmitoleic, linoleic, omega-3, omega-6, arachidonic, linolenic, cis-5,8, 11,14,17-eicosapentae-noic, cis-11,14-eicosadenic, cis-13,16-proxazytoic, docosapentaenoic.